2022
DOI: 10.31235/osf.io/svf4r
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Framework for Infrastructuring Sustainable Innovations in Education

Abstract: Studies on educational technology are often focused on whether a certain technology could improve learning without sufficient consideration of surrounding factors that operate in practice. This paper presents a framework of infrastructuring to expand the scope of educational technology research and development from "things" developed by research teams to include creative design in-use by practitioners. By describing six inter-connected areas of the framework, we highlight ways in which educational technology r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…By stressing educators' interaction in and between activity systems, we extend Bielaczyc's (2013) social infrastructure fourth dimension (in teraction with the outside world) for creating learning environments with technology. Infrastructuring (Chen, 2022;Kashi et al, 2023) as a concept to improve the uptake and sustainability of educational technology projects is a promising framework that seeks to settle out issues that are derived when we focus on the "things" that are part of our interventions. The relational affordances of infrastructuring yield a means of dealing with the issues often encountered when KB com munities grow and develop beyond their initial researcher supported instantiations.…”
Section: Discussionmentioning
confidence: 99%
“…By stressing educators' interaction in and between activity systems, we extend Bielaczyc's (2013) social infrastructure fourth dimension (in teraction with the outside world) for creating learning environments with technology. Infrastructuring (Chen, 2022;Kashi et al, 2023) as a concept to improve the uptake and sustainability of educational technology projects is a promising framework that seeks to settle out issues that are derived when we focus on the "things" that are part of our interventions. The relational affordances of infrastructuring yield a means of dealing with the issues often encountered when KB com munities grow and develop beyond their initial researcher supported instantiations.…”
Section: Discussionmentioning
confidence: 99%
“…This often requires dealing with unanticipated changes, such as sudden bursts of activity, that require attention and intervention. Infrastructuring is carried out by creating researchpractice partnerships (Coburn & Penuel, 2016) with those in authority to shape the existing infrastructures with the aim of building capacity, making instruction more coherent, aligning policies and practice, and disrupting norms that reproduce inequi ties and therefore marginalize specific groups. It is consistent with the goals and focus of design-based implementation research, which is con cerned with developing theory and knowledge about implementation efforts as well as developing the capacity to sustain change within sys tems (Fishman & Penuel, 2018).…”
Section: Why Knowledge Building Infrastructuring?mentioning
confidence: 99%
“…They attributed this gap to the lack of infrastructuring across the school community: The intervention was isolated to one classroom, the principal was supportive but did not fully grasp the approach, parents were relatively uninvolved, and the students' advisor openly criticized the pedagogy in front of the students. Thus, the research ers concluded that the implementation approach in future years had to foster family and communityengagement (Ishimaru, 2019) through a researchpractice partnership (Coburn & Penuel, 2016), whereby parents, school administration, the teaching staff, broader assessment practices, and so on needed to be part of the infrastruc turing process.…”
Section: Fostering a Growth Culture To Support Knowledge Building By ...mentioning
confidence: 99%